2022
DOI: 10.3390/ijerph19031264
|View full text |Cite
|
Sign up to set email alerts
|

Oxysterols Profile in Zebrafish Embryos Exposed to Triclocarban and Propylparaben—A Preliminary Study

Abstract: Oxysterols have long been considered as simple by-products of cholesterol metabolism, but they are now fully designed as bioactive lipids that exert their multiple effects through their binding to several receptors, representing endogenous mediators potentially involved in several metabolic diseases. There is also a growing concern that metabolic disorders may be linked with exposure to endocrine-disrupting chemicals (EDCs). To date, there are no studies aimed to link EDCs exposure to oxysterols perturbation—n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Parabens can disrupt several molecular pathways within cells via ER-mediated or AR-mediated mechanisms, oxidative stress-induced impairment, lysosomal and mitochondrial disorder and DNA damage [ 55 ]. Previous researches demonstrated that PrP induced detrimental influence on zebrafish, including lipid metabolism disorder [ 26 , 56 ], oxidative stress, DNA double-strand breaks and apoptosis [ 28 ]. Studies also suggested that PrP and other parabens may contribute to carcinogenicity [ 55 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parabens can disrupt several molecular pathways within cells via ER-mediated or AR-mediated mechanisms, oxidative stress-induced impairment, lysosomal and mitochondrial disorder and DNA damage [ 55 ]. Previous researches demonstrated that PrP induced detrimental influence on zebrafish, including lipid metabolism disorder [ 26 , 56 ], oxidative stress, DNA double-strand breaks and apoptosis [ 28 ]. Studies also suggested that PrP and other parabens may contribute to carcinogenicity [ 55 , 57 ].…”
Section: Discussionmentioning
confidence: 99%